Agent Based Modeling for Investment and Operational Risk Considerations in Palm Oil Supply Chain - Syarif Hidayat; Ms. Marimin (International Journal of Supply Chain Management, 2014)
In palm oil supply chain (POSC) the investment and operational risk levels between the actors may not be proportionately rewarded by the same levels of added value. However, each actor will attempt to obtain the highest reward. In this study the authors designed a model to simulate the interaction and negotiation behaviors of the actors, and to facilitate optimum distribution of the added value, while considering the successive investment and operational risk levels. Agent-based modeling approach was used for this purpose as it provided the best means to identify and study the supply chain actors (or agents) behaviors. Netlogo software was used to develop the program. This study is important because the model can facilitate further development of various formula to calculate the fair distribution of added value among the actors, therefore ensure the supply chain sustainability. The result of this study indicated that the negotiation between all actors in POSC need to consider overall supply chain sustainability while conducting pairwise negotiation, otherwise the supply chain continuity may be endangered. Keywords - Value added, Palm Oil Supply Chain, business negotiation, Agent Based Modeling, Netlogo software.